Annual Plan 2002-03 Approved Outlay 2002-03 - Planning Commission (Planning Commission, 2002)
I am directed to refer to the discussions held in the Planning Commission at the level of the Deputy Chairman, Planning Commission with the Chief Minister to your State on 3re July, 2002 wherein an outlay of Rs. 10100.00 crore for the Annual Plan 2002-03 V V L4 U VII V IV . The scheme of financing the agreed outlay, is given at Annexure. A statement showing the distribution of agreed plan outlay among different heads and sub-heads of development is enclosed. The earmarked outlays and outlays for different components of PMGY have also been indicated in the statement. I am also to invite your attention to the procedure for sending adjustment proposals, and to request you to send the adjustment proposals for the Annual Plan 2002-03, if any, together with appropriate justification, before 31st January, 2003.
Planning Commission State Plan Division